A Possible Link Between Winter Arctic Sea Ice Decline and a Collapse of the Beaufort High? - Alek A. Petty (Geophysical Research Letters)
Abstract A new study by Moore et al. (2018, https://doi.org/10.1002/2017GL076446) highlights a collapse of the anticyclonic “Beaufort High” atmospheric circulation over the western Arctic Ocean in the winter of 2017 and an associated reversal of the sea ice drift through the southern Beaufort Sea (eastward instead of the predominantly westward circulation). The authors linked this to the loss of sea ice in the Barents Sea, anomalous warming over the region, and the intrusion of low‐pressure cyclones along the eastern Arctic. In this commentary we discuss the significance of this observation, the challenges associated with understanding these possible linkages, and some of the alternative hypotheses surrounding the impacts of winter Arctic sea ice loss.